Hybrid Learning Implementation in STIE Bina Karya during Pandemic - Haya Haratikka; Yenni Arfah; Rapat Piter Sony (Pioneer: Journal of Language and Literature, 2022)
Hybrid learning was expected to overcome the online learning restriction during the pandemic. The purpose of this research was to find out students’ opinions on hybrid learning implementation. This research took forty students who represented all semester of STIE Bina Karya as the respondent. The respondents’ answers in form of words, phrases, and sentences were the data in this study. The data were collected through open-ended questionnaires which were analyzed through thematic analysis. The results showed that hybrid learning implementation in STIE Bina Karya needs to be reconsidered. Both lecture and learners need more adaptation related to the problem which influences the online students. Online class students face more obstacles from inside and outside.